2016
DOI: 10.1016/j.eurpsy.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in bipolar disorder: A systematic review and meta-analysis

Abstract: Our meta-analysis provides evidence that leptin levels are not altered in BD across the mood spectrum compared to healthy controls. The disproportionate increase of leptin levels with increase in BMI in BD speaks in favour of a potential inflammatory role of white adipose tissue in BD and a disproportionate increase of leptin levels with increase in age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
(83 reference statements)
2
22
0
Order By: Relevance
“…Cytokines secreted by adipose tissue are called adipokines. Dysregulation of adipokines has been linked to many disease states such as diabetes and obesity [11] and also to cardiovascular diseases [23], bone diseases [24], carcinogenesis [25], chronic kidney disease [26], sepsis [27], and even bipolar disorder [28]. Remarkably, in our cohorts of critically ill patients due to sepsis and different entities like cardiogenic shock and liver failure, adipokines like adiponectin [29], resistin [18], and leptin [4] have been shown to associate with patient survival, underlining a critical role of adipokines in the progression of sepsis and nonseptic critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines secreted by adipose tissue are called adipokines. Dysregulation of adipokines has been linked to many disease states such as diabetes and obesity [11] and also to cardiovascular diseases [23], bone diseases [24], carcinogenesis [25], chronic kidney disease [26], sepsis [27], and even bipolar disorder [28]. Remarkably, in our cohorts of critically ill patients due to sepsis and different entities like cardiogenic shock and liver failure, adipokines like adiponectin [29], resistin [18], and leptin [4] have been shown to associate with patient survival, underlining a critical role of adipokines in the progression of sepsis and nonseptic critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies showed that leptin levels are increased in major depressive disorders, but only in patients experiencing atypical features, suggesting that leptin may be involved in a subset of patients with increased weight [62,63]. Concerning bipolar disorder, a meta-analysis conducted in 2016, including eleven studies and 1118 participants, provides evidence that leptin levels are not altered in BD when compared to healthy controls [64].…”
Section: Leptin and Psychiatric Illnessesmentioning
confidence: 99%
“… 3 Its role in obesity and reproductive regulation are well known. 4 It appears to function as regulator of food quantity consumed relative to the amount of energy expended. 5 …”
Section: Introductionmentioning
confidence: 99%